Long-term 3-year follow-up of mosunetuzumab in relapsed or refractory follicular lymphoma after ≥2 prior therapies - Sehn, Laurie H.; Bartlett, Nancy L.; Matasar, Matthew J.; Schuster, Stephen J.; Assouline, Sarit E.; Giri, Pratyush; Kuruvilla, John; Shadman, Mazyar; Cheah, Chan Yoon; Dietrich, Sascha; Fay, Keith; Ku, Matthew; et al. (Blood, 2025)
Mosunetuzumab, a CD20×CD3 T-cell engaging bispecific antibody, redirects T cells to eliminate malignant B cells. We present updated efficacy and safety data of a pivotal phase 1/2 study after a median follow-up of 37.4 months in 90 patients with relapsed/refractory (R/R) follicular lymphoma (FL) and ≥2 prior lines of therapy treated with fixed-duration mosunetuzumab. Investigator-assessed complete response (CR) rate and objective response rate were 60.0% (95% confidence interval [CI], 49.1-70.2) and 77.8% (95% CI, 67.8-85.9), respectively. Among 70 responders, median duration of response was 35.9 months (95% CI, 20.7 to not estimable [NE]). Among 54 patients who achieved CR, 49 remained in CR at the end of treatment; median duration of CR was not reached (NR; 95% CI, 33.0 to NE); Kaplan-Meier-estimated 30-month remission rate was 72.4% (95% CI, 59.2-85.6). Estimated 36-month overall survival (OS) rate was 82.4% (95% CI, 73.8-91.0); median OS was NR (95% CI, NE to NE). Median progression-free survival was 24.0 months (95% CI, 12.0 to NE). Median time to CD19+ B-cell recovery was 18.4 months (95% CI, 12.8-25.0) after 8 cycles of mosunetuzumab treatment. No new cytokine release syndrome events or fatal, serious, or grade ≥3 adverse events were reported. With extended follow-up, mosunetuzumab demonstrated high response rates, durable remissions, and manageable safety with no long-term concerns. This supports outpatient mosunetuzumab administration as an off-the-shelf, fixed-duration, safe, and effective treatment for patients with R/R FL, including those with high-risk disease. This trial was registered at www.clinicaltrials.gov as #NCT02500407.
Gesehen am 15.09.2025